Tratamiento selectivo del sotobosque mediterráneo - Cañas J.; Franquesa T. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
We have made selective cuts of bush in mixed Mediterranean forest of Pinus halepensis, Quercus ilex, and Quercus cerrioides in order to get rid of important amounts of dried up Erica arborea a cut down the risk of fire. Our main purpose was to clear the wood so as to let young trees (Quercus ilex, Quercus cerrioides) and typical shrubs related to mature formations (Viburnum tinus, Phillyrea latifolia, Arbutus unedo, etc.) grow. These shrubs could hardly develop before because of competence of Erica arborea. One year after cutting, Erica arborea covers 6 of the surface with a medium size of 45 cm, in some densely populated areas (47.000 plants/hectare). During this period we have observed many germinations, notably of Vibumum tinus and Arbutus unedo.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)